Bimbingan Dan Konseling Islam Bagi Santri Yang Mengalami Homesickness: Pendekatan Psiko-Ekologis - Khasanah, Siti Lailatul (Lembaga Teewan Journal Solutions, 2026)
Homesickness is one of the most common psychological challenges experienced by students in Islamic boarding schools (santri), particularly during the early stages of boarding life. Characterized by longing for family and the home environment, it may negatively affect psychological well-being, self-adjustment, learning motivation, and social interactions. This study aims to identify the psychological and environmental factors contributing to homesickness, describe the implementation of Islamic Guidance and Counseling services in Islamic boarding schools, and formulate a psycho-ecological-based Islamic Guidance and Counseling model. A narrative literature review was conducted using 28 scholarly publications published between 2016 and 2026, retrieved through Google Scholar and Publish or Perish. Data were analyzed using content analysis and thematic synthesis to examine homesickness, psycho-ecological factors, and counseling practices. The findings indicate that homesickness is shaped by the interaction of psychological and environmental factors. Islamic Guidance and Counseling supports students' self-adjustment, psychological well-being, and Islamic character development. A psycho-ecological approach offers a comprehensive counseling framework by fostering collaboration among counselors, families, peers, and the boarding school environment. This integrated model effectively reduces homesickness while strengthening students' adaptation, resilience, and overall psychosocial well-being.